Manajemen Anestesi pada Percutaneus Endoscopic Lumbar Discectomy (PELD) dengan Dexmedetomidine - Sari, Djayanti; Wisudarti, Calcarina Fitriani Retno; Ferdiansyah, David (Jurnal Komplikasi Anestesi, 2022)
The patient is 49 years old with a diagnosis of Hernia Nucleosus Pulposus (HNP) 4-5 lumbar vertebrae. The patient was scheduled to undergo the PELD procedure. The anesthetic technique used is total intravenous anesthesia (TIVA) with dexmedetomidine. The dose used is loading 1 mcg per kg body weight in 10 minutes followed by titration of 0.2-0.7 mcg/kg body weight/hour. During the procedure the operator requires confirmation from the patient to prevent complications of nerve injury. The action lasts about 2 hours in the prone position. The level of sedation was assessed by the Ramsay scale score. Hemodynamics during the procedure is stable and the patient is quite comfortable.